Isolation, genotyping and antibiotic resistance analysis in Salmonella species isolated from turkey meat in Isfahan, Iran - Farhad Lajmorak; Seyedeh Ommolbanin Ghasemian; Majid Gholami-Ahangaran (Heliyon)
Salmonella is one of the mainzoonotic bacteria in the poultry industry.The knowledge about biological characteristics and antibiotic resistance pattern can help medication in poultry and human. This research aimed to study Salmonella spp contamination and its antibiotic resistance in turkey meat in Isfahan province, Iran.400 samples were collected from the turkey meat in slaughter line (May 2021 to May 2022). The conventional microbiological and biochemical tests were applied for isolation and typing of Salmonella spp. The polymerase chain reaction (PCR) was utilized for detection and typing of Salmonella strains. The antibiotic sensitivity test was achieved and all strains were evaluated for resistance genes of Act (3)-IV, Sul1 and qnrA. In microbiological examination, 32 Salmonella strains (8 %) were identified. All tested strains were positive for invA gene. By amplifying the FlicC and Prot6E genes, 28 and 4 strains had genes related to enteritidis and typhimurium, respectively. In disc diffusion test, the highest antibiotic resistance was to oxytetracycline (50 %) and the lowest was to gentamicin, amoxiclavulanic acid, cefotaxime and ceftriaxone. The results showed that 6 (18.75 %) and 10 (31.25 %) of the Salmonella spp were able to amplify Sul1 and qnrA genes, respectively. No Salmonella strain could amplify Act (3)-IV gene. 100 % of the strains carried the Sul1 and qnrA genes were resistant to sulfonamide, and enrofloxacin. Furthermore, 3 sulfonamide resistant strains (75 %) and 5 enrofloxacin resistant strains (83.33 %) were harbored Sul1 and qnrA genes, respectively. The prevalence and antibiotic resistance of Salmonella spp in turkey meat can induce health risk concern. However, the wide spectrum antibiotic resistance complicates the proper treatment of Salmonella infection in human.